2021
DOI: 10.1007/s13280-021-01574-2
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution perception in ten countries during the COVID-19 pandemic

Abstract: As largely documented in the literature, the stark restrictions enforced worldwide in 2020 to curb the COVID-19 pandemic also curtailed the production of air pollutants to some extent. This study investigates the perception of the air pollution as assessed by individuals located in ten countries: Australia, Brazil, China, Ghana, India, Iran, Italy, Norway, South Africa and the USA. The perceptions towards air quality were evaluated by employing an online survey administered in May 2020. Participants (N = 9394)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 126 publications
(122 reference statements)
0
18
0
Order By: Relevance
“…Measured decreases in air pollution at the height of lockdowns were recorded in Australia [32] and worldwide [ 33 , 34 ], following lockdown restrictions, with media reporting on these improvements at the time [50] . Data from an international survey of air quality perception during the lockdown in May 2020 suggested that Australians ( n =387) believed that air pollution levels had decreased compared to before lockdown [53] , although this data uses recall-based changes in perception. Nevertheless, our results showed that air quality concern for health and wellbeing was greater in 2020 than in 2019, although this effect was marginal in the PM 2.5 model.…”
Section: Discussionmentioning
confidence: 99%
“…Measured decreases in air pollution at the height of lockdowns were recorded in Australia [32] and worldwide [ 33 , 34 ], following lockdown restrictions, with media reporting on these improvements at the time [50] . Data from an international survey of air quality perception during the lockdown in May 2020 suggested that Australians ( n =387) believed that air pollution levels had decreased compared to before lockdown [53] , although this data uses recall-based changes in perception. Nevertheless, our results showed that air quality concern for health and wellbeing was greater in 2020 than in 2019, although this effect was marginal in the PM 2.5 model.…”
Section: Discussionmentioning
confidence: 99%
“…The third component of accessing the ability of a city to deal with the air quality issue is its public awareness. Following the tradition in the literature (Liu et al, 2017, Pantavou et al, 2017, Lou et al, 2022, Maione et al, 2021, we have designed a survey with only ten simple questions addressing the perception of the air quality among citizens and how this perception is built, and whether they are taking any measures to avoid detrimental consequences of the air pollution in Lahore city. The questionnaire varied from general public perception of air pollution and public information sources to the self-reported levels of health impact due to air pollution.…”
Section: Public Awarenessmentioning
confidence: 99%
“…Some studies found insignificant changes in SO 2 or PM 10 concentrations (Pei et al 2020 ; Kerimray et al 2020b ; Assanov et al 2021a ; von Schneidemesser et al 2021 ; Bontempi et al 2022 ), which can be explained by the contribution of the non-traffic emissions sources. Despite the decrease in primary pollutants concentrations, it was observed that secondary pollutants levels, such as O 3 increased (Li and Tartarini 2020 ; Sharma et al 2020 ; Kerimray et al 2020b ; Bera et al 2021 ; von Schneidemesser et al 2021 ; Lou et al 2022 ). Zangari et al ( 2020 ) showed no changes in air quality in New York City (USA) during the COVID-19 pandemic and assumed that improvement in air quality could occur in places with high levels of air pollutants compared to locations with relatively clean air.…”
Section: Introductionmentioning
confidence: 99%